Transcriptome Study Of Salmonella Enterica Subspecies Enterica Serovar Typhi Biofilm - Jason, Chin Khee Chian (2018)
Typhoid fever is an acute systemic infection of humans caused by Salmonella enterica subspecies enterica serovar Typhi (S Typhi). During infection the bacteria forms biofilm in the gallbladder to protect itself from the harsh environment of the host. Biofilm formation has been associated with increased resistance towards antibiotics and the host immune system, and promotes bacterial persistence. However, the mechanism of biofilm formation is unknown. High-throughput sequencing using the Illumina HiSeq 2500 platform was performed to study the transcriptome of S. Typhi planktonic, intermediate and mature biofilm cells to identify the genes involved in biofilm formation and to postulate the mechanism of action. Planktonic S.